Deferrable load scheduling of smart meter with intermittent communication connection - Dong, Qiumin (2013)
The demand response program in smart grid implements real-time pricing to reduce power consumption during peak hours. However, sometimes a smart meter cannot receive the price information due to the failure happened in the smart meter's or the neighborhood area network gateway's communication interface. In this paper, we study the deferrable load scheduling problem in a scenario where the data connection used to transmit the price information can be intermittent. We formulate a partially observable Markov decision process (POMDP) model to obtain the optimal price inquiry policy for the smart meter when it cannot receive the real-time price information. Then given the power price information, a Markov decision process (MDP) is formulated and solved for the deferrable load scheduling problem. The numerical results obtained in this paper can be used to set parameters properly according to different scheduling requirement.